(untitled) (mathematica didactica, 2024)
In this study, N = 62 learners in eighth grade of a secondary school in Germany (Gymnasium) were asked about their expectations of success and value beliefs regarding various mathematical topics. The learners also rated three different mathematical tasks and chose one task which they would prefer to work on most. The relationships between their characteristics and their reasons for choosing a task were analyzed. The results show unexpectedly low value beliefs (esp. usefulness) for certain to-pics and indicate that the individual characteristics should be measured differentiated by content area. In addition, most learners justify their choice of the task based on their expectations of success and their assessment of difficulty.